(untitled) - Nguyễn, Nghĩa Dân; Võ, Văn Trực (H., 2011)
TM tài liệu tham khảo Tr. 276 - 277
Keywords: Văn học dân gian -- Ca dao -- Hà Nội (Việt Nam); Việt Nam -- Văn học dân gian -- Ca dao; Ca dao -- Việt Nam